KEANEKARAGAMAN MAKROZOOBENTOS SEBAGAI BIOINDIKATOR DI PERAIRAN ESTUARI SUAKA MARGASATWA KARANG GADING KABUPATEN DELI SERDANG (The diversity of macrozoobenthos as a bioindicator Estuary Waterway Wildlife Karang Gading Deli Serdang) - Rio Fentaria S; Miswar Budi Mulya; Yunasfi Djayus (AQUACOASTMARINE, 2017)
Macrozoobenthos is a living organism attached to the bottom of the water or on the surface of the bottom waters. This study aims to determine the level of macrozoobenthos diversity and water quality based The biodiversity Index This study was conducted in May-June 2015 by using purposive sampling method in five different locations of community activities. The research showed 20 species belonging to the 17 families, 4 orders, and 2 classes. The highest density on the station I found the Anadara cornea species of 171.43 ind/m2, the station II on the Anadara cornea species of 304.76 ind/m2, the station III on the species of Murex trapa amounted to 266.67 ind/m2, the station IV in species Volema Myristica and Anadara cornea of 190.48 ind/m2, the station V on the species Monodonta canalifera of 152.38 ind/m2. The highest diversity index of 2.88 at the station I classified in the level of diversity rate as medium and the lowest at station IV of 2.70 were classified in the level of diversity rate as medium. Uniformity index ranged from 0.92 to 0.96 with the uniformity of species category is relatively evenly distributed. Based on the diversity index is known that the estuarine waters of the Coral Ivory wildlife reserve in the category of medium polluted.Keywords :Macrozoobenthos, Diversity, Pollution Level.